El estrés y su incidencia en la practica pedagógica de los docentes del Colegio Fiscal en Ciencias Juan Montalvo, de la ciudad de Machala, en el periodo lectivo 2012-2013. - Muñoz Jara, Marcia Maribel (2012)
Stress it can be defined as the process that initiates a host of environmental factors that receives the individual and the attitude has to take against these stimuli, launching their coping resources to situations beyond their control, when the excessive demand environment is to have the resources, a series of adaptive reactions resource mobilization, involving physiological arousal, including negative emotional develops.